The nymph of Atopopus tarsalis Eaton, 1881 (Ephemeroptera, Heptageniidae): first description, ecology and behaviour - Sartori, Michel; Derleth, Pascale; Webb, J. M. (Zootaxa, 2007)
The nymph of Atopopus tarsalis Eaton, 1881, type species of the genus, is described in detail for the first time. The egg stage is also presented. Endemic to Borneo, A. tarsalis nymphs exhibit a peculiar behaviour, being able to climb boulders and stay out of the water for periods of at least 20 minutes without dehydration. Hypotheses for such behaviour are briefly discussed such as drift and predation avoidance.